Mechanical Complications of Acute Myocardial Infarction: A Scientific Statement From the American Heart Association. Issue 2 (13th July 2021) - Damluji, Abdulla A.; van Diepen, Sean; Katz, Jason N.; Menon, Venu; Tamis-Holland, Jacqueline E.; Bakitas, Marie; Cohen, Mauricio G.; Balsam, Leora B.; Chikwe, Joanna
Abstract : Over the past few decades, advances in pharmacological, catheter-based, and surgical reperfusion have improved outcomes for patients with acute myocardial infarctions. However, patients with large infarcts or those who do not receive timely revascularization remain at risk for mechanical complications of acute myocardial infarction. The most commonly encountered mechanical complications are acute mitral regurgitation secondary to papillary muscle rupture, ventricular septal defect, pseudoaneurysm, and free wall rupture; each complication is associated with a significant risk of morbidity, mortality, and hospital resource utilization. The care for patients with mechanical complications is complex and requires a multidisciplinary collaboration for prompt recognition, diagnosis, hemodynamic stabilization, and decision support to assist patients and families in the selection of definitive therapies or palliation. However, because of the relatively small number of high-quality studies that exist to guide clinical practice, there is significant variability in care that mainly depends on local expertise and available resources.